Resolusi Konflik Tapal Batas Wilayah Nagari Suliki Dengan Nagari Sungai Rimbang Di Kecamatan Suliki Kabupaten Lima Puluh Kota - Jodi Ramadhan; Endrizal Endrizal; Edi Satria (Universitas Pahlawan Tuanku Tambusai, 2023)
This study discusses the resolution of boundary conflicts between Nagari Suliki and Nagari Sungai Rimbang in Kecamatan Suliki Kabupaten Lima Puluh Kota. The purpose of this study was to describe the background of the boundary conflict between Nagari Suliki and Nagari Sungai Rimbang in Kecamatan Suliki Kabupaten Lima Puluh Kota. The theory used is Wirawan's theory of conflict. The method used is qualitative research. Data collection techniques are field observations, interviews, documentation and literature study. The findings of this study are that the border conflict between Nagari Suliki and Sungai Rimbang Nagari in Suliki Nagari is caused by several factors including rejection of the regent's regulation regarding land boundaries, unilateral claims and economic interests. The impact of this problem is the occurrence of tensions between Nagari Suliki and Sungai Rimbang and a crisis of confidence in the government. Then there are several solutions offered based on the factors that cause the conflict, namely by making losses back to the border, mediation and economic equity. Keywords: Conflict, boundary, conflict resolution